Faith or Works, Which One Saves?: Study of Salvation According to Biblical, A Critical of Progressive Christian Views - Waruwu, Erlina; Hia, Budieli; Damanik, Dapot; Sitopu, Elisamark (Tinta Emas Institute, 2024)
Faith or works, which one saves? This question causes many interpretations from various circles. This research concluded that Progressive Christian Understanding of Salvation is far deviate from biblical. The method used in this research is a qualitative method One of emerging view and phenomenal is a Progressive Christian view which assume that salvation can be obtained by doing good works even outside Christ. If it is happened because of good works, human can do his own effort to get his salvation. However, when human fell into the sin, he tried to strive for his own salvation from the power of death but it was in vain. The sacrifice of Jesus Christ at cross is the only way for human to be safe, redeemed from his sins and got happiness. This research aims to explore about biblical study of salvation. The main source of this research is bible, and also some books, journals, research results related to salvation study, and Progressive Christian church’s view of salvation.